Effect of heat treatment intensity on the survival, activation and subsequent outgrowth of Byssochlamys nivea ascospores. (July 2018) - Samapundo, Simbarashe; Vroman, Annemarie; Eeckhout, Mia; Devlieghere, Frank
Abstract: The objective of this study was to evaluate the combined effects of heat treatment intensity and pH on the activation/inactivation of ascospores of Byssochlamys nivea and their subsequent outgrowth. D-values were evaluated at 85, 90 and 95 °C, whilst activation/inactivation and outgrowth were determined by a full factorial study incorporating (i) heat treatments ranging from no heat treatment to 10 min at 55–90 °C and (ii) pH values ranging from 4 to 6. The estimated D-values were independent of pH and ranged from 1.1 to 1.2 min at 90 °C to 15–16 min at 85 °C. Optimal heat activation was observed when the ascospores were heated for 10 min at 75 °C. Whilst heat activation (10 min at 65–75 °C) did not have a significant effect ( p > 0.05) on the lag phase of B. nivea relative to native ascospores, significantly ( p < 0.05) longer lag phases were observed when heat treatments of 10 min at ≥85 °C were applied. The longest lag phases were observed when the most intense heat treatment evaluated in the study was applied. The results show that reduction of heat treatment intensity could have an impact on the shelf-stability of foods which are contaminated by ascospores of heat resistant moulds. Highlights: Effect of heat treatment intensity and pH on ascospores of B. nivea was evaluated. Optimal activation was observed when ascospores were heated for 10 min at 75 °C. Heat activation (65–75 °C) did not significantly the affect outgrowth of B. nivea . Injury (at ≥85 °C) resulted in significantly longer phases irrespective of the pH. Longest lag phases occurred when ascospores were heated for 10 min at 90 °C.